Funding Contemporary Children's Television: How Digital Convergence Encourages Retro Reboots. Issue 2 (3rd April 2017) - Potter, Anna
ABSTRACT: Contemporary children enjoy abundant supplies of television made especially for them, delivered across multiple platforms by a range of providers that includes public service broadcasters, pay-television services, and subscription video on demand services. Although digital regimes undermined longstanding funding models for children's television and reduced the production of local content in the United Kingdom and Australia, the demands of new market entrant subscription video on demand services striving to establish themselves in global markets have increased the value of the intellectual property of children's screen content. ITV Studios' 2015 re-make of the 1960s Supermarionation series, Thunderbirds, is used here as a case study to illustrate how convergence has contributed to a culture of re-booting in children's television, a genre for which consumer products have long been used to underpin program production costs. Importantly, the licence fees paid by subscription video on demand services—Netflix had a $5 billion programming budget in 2015—have begun to provide additional, significant sources of funding for production budgets, while also ensuring the rapid visibility of program brands in global television markets, particularly the United States. New means of multi-platform distribution also erode the centrality of traditional broadcasters to program commissioning and funding. While this shift in power relations between broadcasters and producers may be welcomed by the production sector, the increasing importance of global subscription video on-demand services in the funding of contemporary children's television poses a threat to locally produced, culturally specific television for children.